Effect of crop geometry, balanced fertilization and agro-chemicals on the yield attributes and yield of fenugreek (Trigonella-foenum graecum) - CHOUDHARY, P D (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during 2 consecutive rabi seasons of 2001-02 and 2002-03 to enhance the productivity of fenugreek through the enjoyment of appropriate crop geometry, balanced fertilization and agrochemicals. Adoption of crop geometry of 30 cm x 10 cm brought about significant increases in seed, haulms and biological yields which tuned to 11.8, 4.8 and 6.4 % respectively over that obtained with the crop geometry of 22.5 cm x 13.3 cm. Mean increases in seed, haulms and biological yields due to application of fertilizer dose of N,, +P,,, + K, + S,, were 57.8, 51.7 and 53.2 % over that recorded with the control. Foliar sprays of thiourea significantly gave higher mean seed yield of 1.87 tonnesha with an increase of 7.8 % over that recorded with the no spray. Corresponding mean increases in haulms and biological yields were 4.20 and 5.01 %.